Aberrant expression of Treg-associated cytokine IL-35 along with IL-10 and TGF-β in acute myeloid leukemia - WU, HAO (D.A. Spandidos, 2012)
Acute myeloid leukemia (AML) is the most common hematological malignancy in adults, characterized by distorted proliferation and the development of myeloid cells and their precursors in the blood and bone marrow. Interleukin 35 (IL-35), a novel inhibitory cytokine secreted by regulatory T (Treg) cells is a novel potential target used for the therapeutic manipulation of Treg activity in order to treat cancer and autoimmune diseases. To investigate the role and imbalance of Treg-related cytokines in the pathogenesis of AML, we measured the plasma concentration of three Treg-associated cytokines [IL-35, IL-10 and transforming growth factor-β (TGF-β)] and evaluated their clinical relevance. The concentration of IL-35, IL-10 and TGF-β in plasma specimens from 55 patients with AML [27 newly diagnosed (ND) patients and 28 in complete remission (CR)] and 24 controls was analyzed using the enzyme-linked immunosorbent assay method. Significantly higher levels of plasma IL-35 and IL-10 were observed in AML ND patients compared with healthy controls or AML CR patients. IL-10 concentrations were positively correlated with TGF-β, whereas no correlations were found between the other cytokines. IL-10 levels were positively correlated with white blood cell (WBC) and neutrophil (NEU) count but there were no correlations between IL-35 and TGF-β with WBC and NEU count. In conclusion, we demonstrated for the first time that AML ND patients have increased plasma concentrations of IL-35, suggesting that this cytokine is involved in the pathophysiological process of the disease, and that further research is required to address this issue.